THE INFLUENCE OF MONEY ETHICS AND INFORMATION TECHNOLOGY TAXATION TO EMBEZZLEMENT TAX (TAX EVASION) MODERATED WITH RELIGIOSITY - Supriatiningsih Supriatiningsih; Azra Aneska; Lady Karlinah; Hidayat Darwis; Samukri Samukri (International Journal Multidisciplinary Science, 2024)
This study aiming to examine the effect of money ethics and tax information technology on tax evasion moderated by religiosity. The population of this study were individual taxpayers located in the areas of Jakarta, Bogor, Depok, Tangerang, Bekasi. This study uses a causal design. The number of individuals taxpayers who were sampled in this study were 145 respondents. The data were processed and analyzed using the Structural Modeling Equating (SEM) technique operated by SmartPLS 4.0 software. Based on the results of the analysis, it shows that money ethics has an effect on tax evasion, tax information technology has no effect on tax evasion, religiosity has note been able to moderate money ethics on tax evasion and religiosity are able to moderate tax information technology on tax evasion.